Fall incidence and associated factors in spinal cord injury patients who walk with or without an ambulatory assistive device - Chaipiphat, Natnaree; Amatachaya, Sugalya; Thaweewannakij, Thiwabhorn; Mato, Lugkana (Journal of Associated Medical Sciences, 2023)
Background: The majority of ambulatory individuals with spinal cord injury (SCI) require an ambulatory assistive device (AAD). However, the association between falls and gait aid use is still inconsistent. Subgroup analysis may provide the opportunity to differentiate these factors more clearly. Objectives: This study aimed to explore fall incidence and associated factors in SCI patients who walk with or without an AAD. Materials and methods: Ninety-seven participants were interviewed for their baseline demographic data, physical activity, history of falling and fear of falling. They were divided into 2 groups, AAD and non AAD group. They were assessed with three functional tests, including the Timed Up and Go Test, Five Time Sit to Stand Test and 10 Meter Walk Test. Then fall data was followed for six months. Results: More than one-third of all participants experienced at least one fall (40%). The results also showed that the proportion of falls in the AAD group was slightly greater than that of the non-AAD group (AAD=46% and non-AAD=32%). In the AAD group, a multiple variable analysis indicated a significantly higher fall rate among those who were younger than 50 years, used a cane or crutches and had moderate to high physical activity. For the non-AAD group, it was found that poor balance and a history of falls were strong factors associated with more falls. Conclusion: Falls were a serious issue for the participants who walk with or without an ADD. However, the factors affecting falls in these two groups were different. Thus, therapists should consider the factors associated with falls for each group of SCI patients separately to provide proper rehabilitation that prevents falls and subsequent injury.